National flood damage evaluation methods: A review of applied methods in England, the Netherlands, the Czech Republik and Germany - Volker Meyer; Frank Messner (UFZ-Umweltforschungszentrum Leipzig-Halle, 2005)
The focus of this guidance document is decision making under uncertainty in river basin management. Our purpose is to give hints for the analysis of decision situations in the HarmoniRiB case studies. The background of HarmoniRiB and thus of the case studies is the implementation of the EU-Water Framework Directive. The directive states the goal that all waters3 in the EU should reach a good status4 by 20155. In order to achieve this goal the member states need to set up river basin districts, each one having a management plan that includes a programme of measures which will achieve good status in the most costeffective manner. We conceptualize this management problem as a decision problem: Which measures should be selected for the programme of measures? The HarmoniRiB case studies are not able to cover all problems of the implementation of the EU-Water Framework Directive in all their complexity. They only investigate certain aspects of this problem. Therefore, we concentrate in this guidance document on a certain type of decision, the selection of management measures to reach a certain goal (this would usually be good status) for the case study river basins. Thereby we put a special focus on uncertainties.
Keywords: 330